Social media for small business : marketing strategies for business owners - Iseli, Franziska (John Wiley, 2021)
"Social Media For Small Business delivers a step-by-step guide to unlocking the potential of social media to grow your business. Award-winning author and entrepreneur Franziska Iseli walks you through how to use Facebook, LinkedIn, Instagram, YouTube, Twitter, and Pinterest to market your small-to medium-sized business ... Perfect for busy business owners, business managers and marketing teams wanting to find new and effective marketing tools to attract more customers, Social Media For Small Business also belongs on the bookshelves of anyone who has difficulty with or wants to learn more about how social media can have a positive impact on their business and brand."--Provided by publisher